Market Opacity and Fragility: Why Liquidity Evaporates When It Is Most Needed - Cespa, Giovanni; Vives, Xavier (American Economic Review, 2026)
Lack of market transparency can impair the liquidity provision of nonstandard liquidity suppliers and make liquidity demand increasing in illiquidity. This can yield strategic complementarities and induce multiple equilibria. Then an initial dearth of liquidity may degenerate into a liquidity rout (as in a “flash crash”), and traders faced with the largest cost of trading are those trading more intensely at equilibrium. An increase in order flow transparency and/or in the mass of dealers who are in the market at all times has a positive impact on total welfare. (JEL G12, G14, G41)